Information System Audit on the Simampu BPBD Web Application of Serang District using the COBIT 5 Framework (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This research was conducted to evaluate the effectiveness and efficiency of the Simampu information system implementation at the Regional Disaster Management Agency (BPBD) of Serang Regency using the COBIT 5 framework. The information system was designed to assist BPBD in disaster data management, reporting, monitoring, and facilitating quick and accurate decision-making. However, the current implementation of Simampu was found to be suboptimal as it is still under development, and several issues were identified, such as system errors, network disruptions, and inadequate data security, hindering effective disaster data processing and reporting. The research utilized a qualitative approach involving direct observations and in-depth interviews with the system management team at BPBD Serang Regency. This study focused on four COBIT 5 domains: BAI01 (Manage Programmes and Projects), DSS02 (Manage Service Requests and Incidents), DSS03 (Manage Problems), and DSS05 (Manage Security Services). These domains were selected due to their relevance to BPBD’s operational needs and strategic objectives in disaster management. Findings revealed several weaknesses in the management of the Simampu information system, particularly concerning IT service management processes, incident handling, problem management, and information security services. To address these weaknesses, the researcher provided technical recommendations, including improvements in data security, network infrastructure enhancements, and optimization of data processing procedures.